O projecto como lugar de encontro: cruzamentos, intersecções, confluências, divergências
Starting from the developing present circumstance we aim to question the project process in the architecture of contemporary times, a situation that stimulates crossings, intersections, confluences and multiple simultaneous divergences. It is interesting to rethink architecture as an experience, which is dependent and conditioned on its circumstance, as opposed to a final and static idea of an architectural object. The following investigation focuses on ways to think, produce and occupy space, always having in consideration the study of the relation between all members that participate in the inhabiting of these spaces and permanently questioning what is the role each one of them occupy in the development of this ongoing process. As these questions are inherently connected to the exercise of the project and its development progress, it seems redundant to attempt answers in the void. It is required to dive into the process of the project to try and understand it better. Or even, to be able to question it better and carefully dissect each vertebra of its skeleton. Coincidental to the start of this thesis arises an opportunity to act, that helps articulate the whole work by complementing it to the shape of this make-project, essential to its development. A request surges - an order - for the drawing of a house to be built. This project is transformed into a central thread of the thesis. The premises concerning the circumstance where it is inserted are fundamental elements that attach the thesis into the project in an almost umbilical way. On the other hand, the project is also a pretext to encourage other study initiatives that, even though emerge from it, find other liberating spaces throughout the thesis. Personifying an ambiguous condition between the academy and the profession, we search the (re)understanding of an idea of architecture, necessarily intersected by the unrolling of the practical exercise we have in our hands. This real and concrete circumstance is disturbed by some assumptions and scenarios that lightly distort it and also locate it in this position between the real and the academic. The work aims to find some clarity in the dense and nebulous process that involves the act of projecting. It is composed as an object that keeps a documental register and organises, simultaneously, the documented process, without wanting to become a register too detailed but that draws on the reflections raised in its development. Thus, the project is serving what we are interested in enhancing and is at the same time, a facilitator.